Mobile Device Interaction with Force Sensing - Scott, James; Brown, Lorna M.; Molloy, Mike (Proceedings of Pervasive 2009, LNCS 5538, 2009)
We propose a new type of input for mobile devices by sensing forces applied by users to device casings. Deformation of the devices is not necessary for such “force gestures” to be detectable. Our prototype implementation augments an ultra-mobile PC (UMPC) to detect twisting and bending forces. We describe examples of interactions using these forces, employing twisting to perform application switching (alt-tab) and interpreting bending as page-down/up. We present a user study exploring users’ abilities to reliably apply twisting and bending forces to various degrees, and draw implications from this study for future force-based interfaces.